Assessment of the Effectiveness of a Pilates Program on Physical Fitness Among Adolescent Students in School - Kaouri, Ifigeneia; Argiriadou, Eirini; Katartzi, Ermioni; Praskidou, Anastasia-Kassiani; Vrabas, Ioannis; Mavrovouniotis, Fotios (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
The purpose of the present study was to examine the effectiveness of a Pilates program in the context of the physical education course at school, on aerobic capacity, muscular strength, muscular endurance, and flexibility of high school students. The voluntary participants were 42 high school students, aged 15 to 17 years, randomly divided into a Pilates group (PG; n = 24) that were taught and practiced Pilates exercises and a control group (CG; n = 18) that participated in the regular physical education school program, during physical education course at school, twice a week, for 45 minutes, for 10 weeks. After the 10-week period, PG significantly improved in all physical fitness parameters, while CG only in muscular endurance. The results demonstrated the very positive effects of the Pilates program as an alternative form of physical activity during the physical education course at school, on physical fitness parameters of high school students.